Tous les garçons et les filles de mon âge? Comics as a nexus to Italian youth media cultures and generational imaginaries - Busi Rizzi, Giorgio; Di Paola, Lorenzo (Elephant & Castle, 2023)
It is difficult to clearly frame the relationships between a medium such as comics and (old and new) generations. Still, the role of comics in defining a generational condition cannot be underestimated. Not only because comics have helped give voice to and show generational similarities and belongings, but also because the imaginary of different generations has manifested itself in the various media practices of consumption and production that have characterized the history of comics. Comics is thus a fertile ground for analysis to investigate the dynamics that contribute to creating that “conception of the world” (Mannheim 1928) capable of orienting young people’s experiences and emotional lives. Thanks to its hybrid nature, its flexibility, and its extraordinary ability to feed on and intertwine with other media, comics thus give us an overview of the fundamental role that media play in shaping the identity of new generations. Through a genealogical reconstruction of the relationships between Italian comics and generational imaginary, we will therefore try to understand how repertoires of memory, symbolic contents, and narratives combine to create, over time, cohorts united by a common sense, an encyclopaedia and a value system that allow mutual recognition among members of the same generation.